A probable case of mutation in Huntington's disease. - Chiu, E (1976)
A patient is described in whom Huntington's disease was diagnosed at the age of 34 years. No evidence of the disorder was found in either parent. Their parentage of the alleged mutant could not be excluded from a study of the inheritance of 25 genetic markers.